Phytoplankton community structure and it’s relationships with water quality in Bangka Island, Indonesia - Muh Yusuf; Robin Robin; Wahyu Adi; Mu’alimah Hudatwi; Widianingsih Widianingsih; Retno Hartati; Robertus Triaji Mahendrajaya; Cristiana Manullang (Marine Science Department Diponegoro University, 2021)
Phytoplankton plays an important role in primary productivity in marine environment. Various environmental changes in coastal area will impact the water quality and their phytoplankton compositions. The purpose of this study is to examine the abundance of phytoplankton from two different sites, i.e Tanah Merah (close to mining site) and Semujur Island (away from mining site) in Bangka Island. Phytoplankton and water sample were collected on June- August 2018. Water quality was measured using water quality checker, whereas the phytoplankton was identified under the microscope with a magnification of 100x. Non-parametric Kruskal test and T-test analysis was performed to determine the abundance, diversity, uniform, and dominance of phytoplankton between Sites, respectively. Statistical analyses showed the abundance of phytoplankton at Semujur Island was significantly higher than that at Tanah Merah (p = 0.003). In additions the diversity, uniform, and dominance were also significantly different between sites (all p <0.05). In Semujur Island, Diatoms (Thalassiothrix, Chaetoceros and Thalassionema) were more dominants than the Dinophyceae group. However, in Tanah Merah, the genera Ceratium belong to class Dinophyceae was more dominant than the class Bacillariophyceae. These results performed that the phytoplankton in Tanah Merah and Semujur Island was affected by environment, in this case the mining area. The water quality in Semujur Island (non-mining Area) might have good quality than in Tanah Merah (mining area). The average value of turbidity and Total Suspended Solid in Tanah Merah Waters causes low abundance of phytoplankton. It can be concluded that tin mining can disrupt the abundance and composition of phytoplankton as a primary producer of waters.